Virtual reference consultation services - Norshahimi, Airul Shazwan; Zanol Rashid, Asma Nadia; Yop, Siti Aqilah (Universiti Teknologi Mara, Kedah, 2022)
Virtual Reference Consultation Services (VFRC) is a service application allowing patrons to connect virtually with the librarian. VFRC is an application that was specially developed with 3D design and space. Virtual Reference Consultation Services is adapted by Virtual Reality (VR) and Augmented Reality (AR) that turns any room into a 3D workspace. VFRC is a new space for library patrons to access the library collections virtually. This product will provide an immersive experience where they can connect their areas easily to other platforms. This product will give online reference and consultation services to library patrons. It also encourages users to seek reference and consulting services remotely. Furthermore, this platform allows libraries and users to collaborate in interactive and immersive platforms. Developers created one special room for the reference consultation services, allowing library patrons to walk around and interact in VFRC virtual rooms with avatar functionality and controls to share, collaborate or view the content with others. This platform can enrich the patron’s library experience and introduce them to the virtual world.